IMPLEMENTASI PELAJARAN TAMBAHAN KOMPUTER DI SD NEGERI 242 PALEMBANG DALAM MENINGKATKAN PROGRAM KURIKULUM 2013 - Irianisyah, Sri (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The experiment was conducted at state elementary school of 242 Palembang. The study was conducted over 3 months. Subjects were students of class V. amounting to as many as 35 people, consisting of 16 female students and 19 male students. Data obtained from the students involved in this study at state elementary school of 242 Palembang, observer and parties other related parties. Techniques of data collection by way of tests and observation. The indicators that are expected in the study of this class action is the accurrence of 70% increase in learning outcomes students achieve mastery learning. The results of this study for 88.57% of the students have completed study and 11.43% of students do not pass the study. This number clearly shows that there has been a significant and the results are in accordance with the expectation that student's mastery of 80%.